A Comprehensive Review on Bio-Based Materials for Chronic Diabetic Wounds - Jinjin Pei; Chella Perumal Palanisamy; Phaniendra Alugoju; Naga Venkata Anusha Anthikapalli; Prabhu Manickam Natarajan; Vidhya Rekha Umapathy; Bhuminathan Swamikannu; Selvaraj Jayaraman; Ponnulakshmi Rajagopal; Sirilux Poompradub (Molecules, 2023)
Globally, millions of people suffer from poor wound healing, which is associated with higher mortality rates and higher healthcare costs. There are several factors that can complicate the healing process of wounds, including inadequate conditions for cell migration, proliferation, and angiogenesis, microbial infections, and prolonged inflammatory responses. Current therapeutic methods have not yet been able to resolve several primary problems; therefore, their effectiveness is limited. As a result of their remarkable properties, bio-based materials have been demonstrated to have a significant impact on wound healing in recent years. In the wound microenvironment, bio-based materials can stimulate numerous cellular and molecular processes that may enhance healing by inhibiting the growth of pathogens, preventing inflammation, and stimulating angiogenesis, potentially converting a non-healing environment to an appropriately healing one. The aim of this present review article is to provide an overview of the mechanisms underlying wound healing and its pathophysiology. The development of bio-based nanomaterials for chronic diabetic wounds as well as novel methodologies for stimulating wound healing mechanisms are also discussed.